2017
DOI: 10.1002/esp.4233
|View full text |Cite
|
Sign up to set email alerts
|

Application of a simple headcut advance model for gullies

Abstract: Gully erosion begins in streambanks and uplands as a consequence of adjustments in driving forces on the landscape imposed by changes in land use or climate. The deleterious effects of gullies worldwide have led to many site-specific studies of gully form and function. In the continental United States, gully erosion in agricultural land has destroyed valuable farmland yet, prediction of gully processes remains problematic on a national scale. This research has proposed a simple method to predict gully headcut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 101 publications
(193 reference statements)
0
16
0
Order By: Relevance
“…Therefore, the plunge pool advanced due to the change in the entrance angle and position of the jet flow (Stein et al, ). Compared with the absence of roots in the bare land plots, the presence of a root system influenced the headcut retreat and was conducive to the formation of a hanging soil‐root matrix at the gully head (Allen et al, ; Rengers & Tucker, ). Moreover, the GRD suddenly increased by a considerable distance once the hanging soil‐root matrix collapsed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the plunge pool advanced due to the change in the entrance angle and position of the jet flow (Stein et al, ). Compared with the absence of roots in the bare land plots, the presence of a root system influenced the headcut retreat and was conducive to the formation of a hanging soil‐root matrix at the gully head (Allen et al, ; Rengers & Tucker, ). Moreover, the GRD suddenly increased by a considerable distance once the hanging soil‐root matrix collapsed.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, land surface coverage has proven to be a strongly related factor that influences the gully erosion rate and topographical threshold conditions for gully head development (Hayas et al, ; Li et al, ; Mukai, ). On the other hand, the effect of vegetation on reducing gully erosion is mainly due to the increase in soil resistance, which potentially depends on root characteristics (Allen, Arnold, Auguste, & Dunbar, ; Knapen, Poesen, Govers, Gyssels, & Nachtergaele, ; Torri et al, ; Vannoppen, Vanmaercke, De Baets, & Poesen, ). Different plant species have different root tensile strengths (De Baets et al, ), and plant species with fibrous roots provide greater additional cohesion in soil (Zegeye et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models employ conservation equations, fluvial (advective) processes, mass-wasting (diffusive or discrete) processes, and various criteria for the initiation of a channel that could migrate upstream with time (De Ploey, 1989;Willgoose et al, 1991a, Willgoose et al, 1991bHoward, 1994Howard, , 1999Bull and Kirkby, 1997;Sidorchuk and Sidorchuk, 1998;Kirkby and Bull, 2000;Sidorchuk, 2005). Recent landscape evolution models now include a gully headcut advance mechanism that considers the combined effects of plunge-pool scour and mass failure 48 S. J. BENNETT AND R. R. WELLS (Alonso et al, 2002;Istanbulluoglu et al, 2005;Flores-Cervantes et al, 2006;Rengers andTucker, 2014, 2015;Allen et al, 2018), which have been supported by specially-designed experiments . As noted by Vanmaercke et al (2016), rates of gully headcut advance are very sensitive to rainfall intensity.…”
Section: Gully Erosion Prediction Technologymentioning
confidence: 99%
“…Gully headcut erosion induced by concentrated flow that is generated from the loesstableland is the main source of soil erosion in the loess tableland and gully region of the Loess Plateau, and thus the improvement in soil resistance of gully heads to concentrated flow is essential for controlling gully headcut erosion. Previous studies have indicated that vegetation restoration at gully heads is conducive to improving soil anti-erodibility and controlling gully head migration (Guo et al, 2018;Allen et al, 2017). However, few studies have been conducted to evaluate the effects of vegetation restoration at gully heads on soil resistance to concentrated flow erosion.…”
Section: Introductionmentioning
confidence: 99%